Políticas migratorias adoptadas en el Ecuador y el derecho a la libre movilidad humana. - Maldonado, Byron E. (2020)
Starting with the Constitution of the Republic of Ecuador (2008), free human mobility has materialized as a constitutional right and a special duty to protect the State. To do this, a doctrinal, jurisprudential, national and international regulations, and others pertinent to the legal field in question, were carried out, from a qualitative, documentary and descriptive methodology, which allowed the documents to be analyzed, a conceptual and practical approach to each one. of the aforementioned institutions, analyzing their nature, origin and special features developed by constitutional doctrine and jurisprudence, under the theory of fundamental rights in general, and the theory of principles in particular. Likewise, the migratory flow that Ecuador has suffered in the last decade has made visible that the lack of public policies in the protection of human rights has caused discriminatory and threatening acts against the dignity of the people, mainly Venezuelan citizens. For this reason, the international organizations for the protection of human rights have indicated that in each State party to this system, they must incorporate into their internal regulations legal mechanisms that prevent abusive and arbitrary behavior against migratory groups. This research is structured by three chapters, in the first the migration policy of the Ecuadorian State was described, in the second the content and scope of free human mobility was studied and in the third the determination of the mechanisms for the protection of the right to free human mobility in the face of migration policies.